Penanaman Karakter Peduli Lingkungan Pada Anak-Anak Melalui Program “Green And Clean” - Martauli, Elvin Desi; Sihaloho, Nani Kitti; Eduard (Jurnal Pengabdian Bukit Pengharapan, 2022)
Character is something that happens to humans created in their childhood home environment. Character, on the other hand, is something that everyone is born with. Character education, including character education in schools, can help shape good character. Character education can be achieved through the development of character values ​​in students. One of the traits that must be created from an early age is the character of love for the environment. The “green and clean” program is one of the techniques to create an atmosphere of loving the environment. The “green and clean” program seeks to encourage children to appreciate their environment from an early age and be able to take care of the beauty of the environment, starting in the school environment. The “green and clean” strategy is implemented in the classroom through a pre-learning program that invites children to participate in activities that cover aspects of K3 (Cleanliness, Beauty, Neatness). The curriculum involves combining picket lines in and around the school, as well as learning to care for plants in front of the class. This program can also increase and increase students' knowledge that a clean and attractive atmosphere can increase students' comfort in carrying out school activities, especially in learning programs. This Community Service Activity (PKM) will be held at SD 020254 Binjai City.